Ecological integrity and global governance science, ethics and the law - Westra, Laura (Routledge research in international environmental law., 2016)
This book argues that, in the face increasing environmental challenges, it is essential to recognise the role that ecological integrity has played, and must play, in governance for environmental sustainability in order to ensure the future survival of life on earth. Ecological integrity encompasses not only the necessity of respect for nature, but also the human right to a sound and healthy environment.